What lies beyond the built environment? Exploring "walkability" across the Detroit region. (April 2022) - Lee, Jieun; Vojnovic, Igor; Grady, Sue C.
Abstract: Despite a long history of research on the influence of the built environment on travel, studies on urban form and pedestrian activity in neighborhoods characterized by rapid decline, as evident across U.S. Midwest cities, remain under-represented in the literature. Moreover, detailed exploration of travel inequities experienced by the socioeconomically disadvantaged is even rare. In examining travel, this research measures precise variations in the built environment—with the use of Road Network Buffers—across Detroit (Michigan) region neighborhoods, including in those experiencing severe disinvestment. This study reconfirms that compact urban form promotes non-automobile travel, and reaffirms the importance of a more balanced residential, retail and commercial land use mix in encouraging pedestrian activity, although it also identifies caveats for those neighborhoods experiencing decline. The research also contributes to expanding our understanding of travel behaviors within the context of amenity disparities and abandonment in neighborhoods experiencing severe disinvestment and extreme income divergence. Intersecting the sociodemographic dimensions and the built environment allows a deeper understanding of much disregarded nuance of travel amongst lower-income, racial minorities in highly segregated urban neighborhoods. Highlights: Exploring individual travel behavior in urban neighborhoods experiencing disinvestment and decline. Intersecting income and race with the built environment to better understand urban travel behavior. Investigating the role of abandonment and poor access to urban amenities on individual travel. Utilizing a GIS-enabled fine geographic scale (Road Network Buffers) to model urban form. Confirming that compact urban form, more balanced retail and commercial land uses in particular, promotes pedestrian activity across the Detroit region.